2017
DOI: 10.5194/acp-17-2067-2017
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the ship contribution to the aerosol of the central Mediterranean

Abstract: Abstract. Particulate matter with aerodynamic diameters lower than 10 µm, (PM 10 ) aerosol samples were collected during summer 2013 within the framework of the Chemistry and Aerosol Mediterranean Experiment (ChArMEx) at two sites located north (Capo Granitola) and south (Lampedusa Island), respectively, of the main Mediterranean shipping route in the Straight of Sicily.The PM 10 samples were collected with 12 h time resolutions at both sites. Selected metals, main anions, cations and elemental and organic car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 75 publications
0
20
2
Order By: Relevance
“…They all correlate quite well with Al (linear correlation coefficients ranging between 0.55 and 0.80) showing that mineral dust is also a major source contribution for these elements. Nevertheless, as shown in previous works [132], they also arose from anthropic activities, such as ship emissions, since they are also present in heavy oil used as fuel for ships. On the basis of Moreno et al [74], particular La/Ce and La/V ratios can be used to identify the samples characterized by a significant contribution from ship emissions; by taking into account these ratios (La/Ce between 0.6 and 0.8 and La/V lower than 0.1), about the 30% of the samples here analyzed can be related to a relevant contribution of ship emissions.…”
Section: Element Concentrationsmentioning
confidence: 69%
“…They all correlate quite well with Al (linear correlation coefficients ranging between 0.55 and 0.80) showing that mineral dust is also a major source contribution for these elements. Nevertheless, as shown in previous works [132], they also arose from anthropic activities, such as ship emissions, since they are also present in heavy oil used as fuel for ships. On the basis of Moreno et al [74], particular La/Ce and La/V ratios can be used to identify the samples characterized by a significant contribution from ship emissions; by taking into account these ratios (La/Ce between 0.6 and 0.8 and La/V lower than 0.1), about the 30% of the samples here analyzed can be related to a relevant contribution of ship emissions.…”
Section: Element Concentrationsmentioning
confidence: 69%
“…Aksoyoglu et al (2016) showed that ship emissions in the Mediterranean may contribute up to 60 % of sulfate concentrations, as SO 2 is a major pollutant emitted from maritime transport. However, in comparison to on-road vehicles, ship emissions are still poorly characterized (Berg et al, 2012). Furthermore, the multiplicity of Mediterranean pollution sources and their interactions makes it difficult to quantify ship contributions to aerosol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…There is a good correlation (R 2 > 0.99 and R 2 > 0.98, P < 0.01) between cation and anions (equivalent concentration) in PM 1.0 and PM 2.5 , respectively, implying a high quality of data and the same source of major ions in this cruise (Fig. S5a) (Boreddy and Kawamura, 2015). Additionally, the relationship between NH + 4 and Ca 2+ vs.…”
Section: Chemical Composition Of Fine Particles During the Yrc And Comentioning
confidence: 72%